The water release schedule for rice production in winter-spring 2020-2021 for the Red River Delta and Northern Midlands Region-Vietnam - CGIAR Research Program on Climate Change, Agriculture and Food Security (2020)
A directive (based on CS-MAP recommendations) was issued by the Ministry of Agriculture and Rural Development instructing local authorities of water release schedule for rice production in winter-spring 2020-2021 in the region.